2012
DOI: 10.1085/jgp.201210847
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structural basis for differential KCNQ1 modulation by KCNE1 and KCNE2

Abstract: KCNE1 associates with KCNQ1 to increase its current amplitude and slow the activation gating process, creating the slow delayed rectifier channel that functions as a “repolarization reserve” in human heart. The transmembrane domain (TMD) of KCNE1 plays a key role in modulating KCNQ1 pore conductance and gating kinetics, and the extracellular juxtamembrane (EJM) region plays a modulatory role by interacting with the extracellular surface of KCNQ1. KCNE2 is also expressed in human heart and can associate with KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 42 publications
(98 reference statements)
7
27
0
Order By: Relevance
“…It is also associated with KCNQ1 (potassium voltage-gated channel, KQT-like subfamily, member 1) and suppresses its current amplitude, which results in slowing down the deactivation gating process. 21 Loss of function of any of those 3 proteins (KCNE2, KCNH2, and KCNQ1) may lead to cohort. Afterwards, owing to a very high-effect size, it could potentially be translated into clinical practice, if only appropriate methods are developed.…”
Section: Resultsmentioning
confidence: 99%
“…It is also associated with KCNQ1 (potassium voltage-gated channel, KQT-like subfamily, member 1) and suppresses its current amplitude, which results in slowing down the deactivation gating process. 21 Loss of function of any of those 3 proteins (KCNE2, KCNH2, and KCNQ1) may lead to cohort. Afterwards, owing to a very high-effect size, it could potentially be translated into clinical practice, if only appropriate methods are developed.…”
Section: Resultsmentioning
confidence: 99%
“…G-V relationships show that there is no significant shift in the Previously, residue F57 had been shown to interact with KCNQ1 in the resting state of the channel (25,26). As KCNE1 is proposed to shift and rotate within the clefts of the KCNQ1 tetramer during activation (16,17), the unnatural amino acid cross-linking technique was used to investigate the state-dependent interactions that might occur between these subunits. Upon excitation with UV light (350-380 nm), Bpa forms a covalent cross-link with a C-H bond within a 3.1 Å radius (31).…”
Section: F57bpa Kcne1 Cross-links To Kcnq1 In the Resting Statementioning
confidence: 99%
“…Various studies have suggested regulatory interactions occur between KCNE1 and the KCNQ1 tetramer at both the VSD and the pore domain. Using a chimeric approach and scanning mutagenesis, interactions have been identified between KCNE1 and the pore domain of KCNQ1 (14)(15)(16). Whereas the extracellular end of the b-subunit transmembrane domain was shown to interact with the extracellular end of the S1 domain of KCNQ1 (17), cysteine scanning mutagenesis experiments and computational models have shown that KCNE1 comes into close contact with the voltage sensor, S4, in KCNQ1 (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BK channels can be modulated simultaneously by both the BKβ and BKγ subunits, which are thought to associate with the pore-forming subunits via transmembrane domains (Gonzalez-Perez et al, 2015;Gonzalez-Perez and Lingle, 2019;Aldrich, 2012, 2010) . Similarly, the widely studied KCNE subunits are transmembrane proteins that have been proposed to integrate into clefts between neighboring voltage-sensing domains to modulate channel function (Murray et al, 2016;Wang et al, 2012;Xu et al, 2013) . Another Kv channel with prominent regulation of channel gating by multiple classes of regulatory proteins is the Kv4 family, which is sensitive to both KChIP (a soluble cytoplasmic protein) and DPP-like proteins (transmembrane), leading to modulation of channel expression and gating (Jerng et al, 2005;Kitazawa et al, 2015;Zagha et al, 2005) .…”
Section: Discussionmentioning
confidence: 99%